(untitled) (Malaysian Management Journal, 2014)
This paper empirically examines the relationship between excess capacity and probability of entry into Malaysian palm oil refining industry using time series data. Capacity and production, two components crucial to the study of excess capacity, were included in the estimation model. The analysis was conducted specifically in the Malaysian palm oil refining industry and the sample covered the period from 1976 to 2011. Logit model was employed in this analysis, where the results exhibited that excess capacity does not significantly influence probability of entry into the palm oil refining industry in Malaysia.